A genetic regulatory see-saw of biofilm and virulence in MRSA pathogenesis - Patel, Hardi; Rawat, Seema (Frontiers in Microbiology, 2023)
Staphylococcus aureus is one of the most common opportunistic human pathogens causing several infectious diseases. Ever since the emergence of the first methicillin-resistant Staphylococcus aureus (MRSA) strain decades back, the organism has been a major cause of hospital-acquired infections (HA-MRSA). The spread of this pathogen across the community led to the emergence of a more virulent subtype of the strain, i.e., Community acquired Methicillin resistant Staphylococcus aureus (CA-MRSA). Hence, WHO has declared Staphylococcus aureus as a high-priority pathogen. MRSA pathogenesis is remarkable because of the ability of this “superbug” to form robust biofilm both in vivo and in vitro by the formation of polysaccharide intercellular adhesin (PIA), extracellular DNA (eDNA), wall teichoic acids (WTAs), and capsule (CP), which are major components that impart stability to a biofilm. On the other hand, secretion of a diverse array of virulence factors such as hemolysins, leukotoxins, enterotoxins, and Protein A regulated by agr and sae two-component systems (TCS) aids in combating host immune response. The up- and downregulation of adhesion genes involved in biofilm formation and genes responsible for synthesizing virulence factors during different stages of infection act as a genetic regulatory see-saw in the pathogenesis of MRSA. This review provides insight into the evolution and pathogenesis of MRSA infections with a focus on genetic regulation of biofilm formation and virulence factors secretion.